The study of environmentally-friendly funds. - Lin, Jimmy Jinlong. (2008)
This paper aims to study the performance of Environmentally Friendly investments, specifically in the form of Environmentally Friendly mutual funds. Numerous previous studies have been done on Socially Responsible Investments (SRI), yielding different conclusions on the advantages and disadvantages of investing ethically. However, few studies have concentrated their focus on Environmentally Friendly investments. Therefore, this study employed a sample of 120 funds available on Bloomberg that were categorized as “Environmentally Friendly” and compared them with market indices according to their geographical focus. Using a sample period from December 6th, 2004 to December 6th, 2007, the fund performances were measured using the Sharpe Ratio, Treynor Index and Jensen’s Alpha. Our results found that the Environmentally Friendly funds yielded average returns that were either higher than the benchmarks or not significantly different from them.